Acute shortening and subsequent lengthening of the radius and ulna for the treatment of an infected nonunion in a dog. - Rahal, S C (2001)
A 3-year-old, male crossbred dog with osteomyelitis of the radius and ulna was treated using Ilizarov's method. Two centimeters of infected bone was resected, then acute bone shortening and subsequent lengthening of a healthy bone site were performed. The infection was eradicated, but a residual leg-length discrepancy was present.